HEREDITARY ENDOCRINE TUMOURS: CURRENT STATE-OF-THE-ART AND RESEARCH OPPORTUNITIES: Challenges and opportunities in genetic counseling for hereditary endocrine neoplasia syndromes. Issue 8 (August 2020) - Brock, Pamela; Geurts, Jennifer L; Van Galen, Paulien; Blouch, Erica; Welch, James; Kunz, Amy; Desrosiers, Lauren; Gauerke, Jennifer; Hyde, Samuel
Abstract : The Genetic Counseling Working Group from the 16th International Workshop on Multiple Endocrine Neoplasia (MEN 2019) convened to discuss contemporary challenges and opportunities in the area of genetic counseling for individuals and families affected by hereditary endocrine neoplasia syndromes. As healthcare professionals with multidisciplinary training in human genetics, risk assessment, patient education, psychosocial counseling, and research methodology, genetic counselors bring a unique perspective to working toward addressing these challenges and identifying their subsequent opportunities. This Working Group focused on the following broad areas: (1) genetic counseling resources for endocrine neoplasias, (2) candidate gene discovery, (3) implications of increasingly sensitive and expansive genetic testing technologies for both the germline and the tumors, and (4) situating clinical diagnoses for hereditary endocrine neoplasia syndromes in the context of present-day knowledge.